Philosophical practice - Marinoff, Lou (Academic Press, 2002)
This book provides a look at philosophical practice from the viewpoint of the practitioner or prospective practitioner. It answers the questions: What is philosophical practice? What are its aims and methods? How does philosophical counseling differ from psychological counseling and other forms of psychotherapy. How are philosophical practitioners educated and trained? How do philosophical practitioners relate to other professions? What are the politics of philosophical practice? How does one become a practitioner? What is APPA Certification? What are the prospects for philosophical practice in the USA and elsewhere? Handbook of Philosophical Practice provides an account of philosophy's current renaissance as a discipline of applied practice while critiquing the historical, social, and cultural forces which have contributed to its earlier descent into obscurity.